Secondary antibody deficiency in chronic lymphocytic leukemia and non-Hodgkin lymphoma: Recommendations from an international expert panel. (March 2023) - Jolles, Stephen; Giralt, Sergio; Kerre, Tessa; Lazarus, Hillard M.; Mustafa, S. Shahzad; Papanicolaou, Genovefa A.; Reiser, Marcel; Ria, Roberto; Vinh, Donald C.; Wingard, John R.
Abstract: Lymphoid hematologic malignancies (HMs) and their treatment may result in secondary antibody deficiency (SAD), which is associated with an increased risk and susceptibility for recurrent and/or severe infections. Infection-related morbidity and mortality are major concerns when managing patients with HMs. The HM treatment landscape continues to evolve at a rapid pace, thereby necessitating the need for up-to-date guidance on how best to recognize, diagnose, treat, and monitor patients at risk of developing SAD. This consensus review, from a panel of international experts, aims to address this challenge by raising awareness of SAD and providing practical recommendations on SAD diagnosis and management. SAD evaluation is recommended at diagnosis of lymphoid HM in all patients, irrespective of infection history, to risk-stratify and define disease versus treatment-related SAD. Our recommendations promote a proactive and individualized approach to patient management to reduce infection risk and improve outcomes. Highlights: Lymphoid hematological malignancies may cause secondary antibody deficiency. Secondary antibody deficiency is the most common type of secondary immunodeficiency. Secondary antibody deficiency is linked with high infection risk and mortality. At diagnosis, test CLL and NHL patients for secondary antibody deficiency. Proactive care for secondary antibody deficiency aims to reduce infection risk.